The Effect of Principal Leadership, Ethos, and Work Climate on Educator Performance MAN District of Sumedang - Riyanti, Triska; Hidayatulloh, Rochmat; Hidayat, Wahyu (ISLAMIKA, 2024)
Education is seen as a valuable investment in improving the quality of human resources and building a nation. The research focuses on the MAN Se-Kab district of Sumedang to analyze the leadership of the head of the school, the work ethos, the working climate, and the performance of the educators. Quantitative survey methods are used with data collection using lifts. Data analysis includes validity, reliability, classical assumption tests, double linear regression, and hypothesis tests. Research at MAN Se-Kab district Sumedang found that the leadership of the head of school, the work ethos, and the working climate were rated "Good" (average 4.24, 4.58, and 4.27), as well as the performance of educators. (rata-rata 3,90). Nevertheless, the leadership of the head of the school did not significantly impact the teacher's version (t count -1,035 < 2,012, significance 0,306 > 0,05). On the contrary, the work ethos (2,621, significance 0.042 < 0,05) and the working climate (2,047, signification 0.053 < 0.05) had a significant positive impact. Simultaneously, the three variables influence the performance of educators (f counts 10,890 > f table 4,052, significance 0,045 < 0,05). The determination coefficient of 30.4% suggests that the head of school leadership, work ethos, and work climate variables can explain variations in teacher performance. In comparison, the other 34.8% variations are influenced by external factors such as culture and environment. Research recommendations include improved teacher performance and the role of the head of school in creating a productive working environment. The study provides in-depth insight into education dynamics in the MAN Se-Kab district of Sumedang, providing a basis for improving the quality of educators' performance and leadership.